Hydrologic Controls of Methane Dynamics in Karst Subterranean Estuaries. Issue 12 (7th December 2018) - Brankovits, D.; Pohlman, J. W.; Ganju, N. K.; Iliffe, T. M.; Lowell, N.; Roth, E.; Sylva, S. P.; Emmert, J. A.; Lapham, L. L.
Abstract: Karst subterranean estuaries (KSEs) extend into carbonate platforms along 12% of all coastlines. A recent study has shown that microbial methane (CH4 ) consumption is an important component of the carbon cycle and food web dynamics within flooded caves that permeate KSEs. In this study, we obtained high‐resolution ( 2.5‐day) temporal records of dissolved methane concentrations and its stable isotopic content (δ 13 C) to evaluate how regional meteorology and hydrology control methane dynamics in KSEs. Our records show that less methane was present in the anoxic fresh water during the wet season (4, 361 ± 89 nM) than during the dry season (5, 949 ± 132 nM), suggesting that the wet season hydrologic regime enhances mixing of methane and other constituents into the underlying brackish water. The δ 13 C of the methane (−38.1 ± 1.7‰) in the brackish water was consistently more 13 C‐enriched than fresh water methane (−65.4 ± 0.4‰), implying persistent methane oxidation in the cave. Using a hydrologically based mass balance model, we calculate that methane consumption in the KSE was 21–28 mg CH4 ·m − 2 ·year − 1 during the 6‐month dry period, which equates to 1.4 t of methane consumed within the 102‐ to 138‐km 2 catchment basin for the cave. Unless wet season methane consumption is much greater, the magnitude of methane oxidized within KSEs is not likely to affect the global methane budget. However, our estimates constrain the contribution of a critical resource for this widely distributed subterranean ecosystem. Plain Language Summary: Subterranean estuaries occur worldwide where fresh and marine‐derived waters mix within coastal aquifers, creating a chemical reaction zone that alters the composition of materials transported to the sea. According to a recent study, methane—a potent greenhouse gas—and the bacteria that feed on it form the basis of a complex food web restricted to cave networks flooded by the subterranean estuary. Questions about the seasonality and magnitude of this methane sink remain unclear. Unprecedented chemical records collected during this study with simultaneous meteorological and hydrological data reveal that methane accumulation is significantly greater during the dry season than during the wet season when rainfall is more prevalent and greater mixing in the coastal aquifer facilitates methane consumption. We estimate that 1.4 t of methane are consumed during a 6‐month‐long dry period within the 100‐km 2 catchment region. This estimate constrains the contribution of a critical energy source for karst subterranean estuary ecosystems. Key Points: Concurrent meteorological, hydrological, and chemical records are used to study sources and sinks of methane in a karst subterranean estuary Increased precipitation enhances methane oxidation by mixing anoxic methane‐rich waters with oxygenated waters A hydrologically based mass balance model provides a first‐order estimate for the magnitude of the methane sink within the catchment region